Astheria: a semiótica e o design de narrativa no desenvolvimento de um jogo independente de valor agregado - Braga, Maria Lilian Sadala (Brasil, 2025)
The research develops a value-added video game proposal, Astheria, using concepts of semiotics and narrative design, with the goal of enhancing the quality and competitiveness of indie games in the Brazilian market. In a scenario of emerging indie studios facing economic and structural challenges to achieve global recognition, the research begins with a theoretical foundation on the highlighted topics and a qualitative approach to investigate how these tools can positively impact the perceived value of games, both from the player's and investor's perspectives. Data on the target audience was collected through an online questionnaire to validate player preferences and interests, aligning the game proposal with market expectations. Following this, a project methodology combining the approaches of Bomfim (1995) and Pires et al. (2020) was applied, enabling the complete development of Astheria's concept, from its main characters and storyline to the creation of a simulated pitch aimed at game industry investors. As a result, the research demonstrated that the application of semiotics and narrative design can effectively add value to the player experience, resulting in a financial viability of the game above typical standards in the national industry, proving that such techniques are essential for creating indie games with global market potential.